Extent of therapeutic support in Positive Psychotherapy: A randomized comparative efficacy study for the treatment of anxiety disorders in an online group setting - Catiana L. Engelhardt; Sabrina Keller; Thomas Berger; Anton-Rupert Laireiter (PLoS ONE, 2026)
Objective Positive Psychotherapy (PPT) is increasingly being studied as a potential treatment option for psychological diseases. In recent years the internet has been incorporated into traditional face-to-face therapy which, if successful in its treatment outcome, could lead to a more economic and affordable therapy since a certain proportion of therapy could be done without real-time therapist contact. The aim of this study is to investigate whether significant differences in outcome are found when comparing the effectiveness of PPT with complete therapeutic support (cPPT) in treating anxiety disorders compared to PPT with minimal therapeutic supervision (mPPT) in an online group setting. Participants in the cPPT group took part in ten weekly 120-minute online sessions with a therapist, while the mPPT group only had three 60-minute online sessions. For the remaining seven sessions, participants received videos. This paper presents the outcomes of both groups. Methods This randomized controlled trial involved 106 participants allocated into either a group with complete therapeutic support (cPPT; n = 53) or a group with minimal supervision (mPPT; n = 53) for ten weeks. Data collection occurred through online questionnaires, evaluating anxiety levels, subjective happiness, quality of life, and psychological distress. These assessments were conducted at three time points: baseline (T0), post-intervention (T1), and three-month follow-up (T2). Results Significant improvements over time were observed in both the cPPT and mPPT groups across several outcomes. Anxiety symptoms decreased substantially from pre-treatment to post-treatment and remained stable at the three-month follow-up. Significant time effects were found for fear and anxiety-related outcomes, including FQ ( η 2 = 0.10 , η w 2 = 0.32 ), BAI ( η 2 = 0.17 , η w 2 = 0.42 ), PAS ( η 2 = 0.14 , η w 2 = 0.39 ), GAD-7 ( η 2 = 0.16 , η w 2 = 0.36 ), with gains maintained at the three-month follow-up. Positive psychological outcomes also improved significantly over time. Significant effects were observed for subjective well-being and flourishing, including PPTI ( η 2 = 0.04 , η w 2 = 0.15 ), FS ( η 2 = 0.02 , η w 2 = 0.07 ), and SWLS ( η 2 = 0.04 , η w 2 = 0.14 ). Psychological distress likewise decreased significantly across treatment. Significant time effects were found for ISR ( η 2 = 0.11 , η w 2 = 0.29 ), PHQ-9 ( η 2 = 0.06 , η w 2 = 0.17 ), with improvements remaining stable at follow-up. In all cases, there were no significant group × time interactions, indicating that the mPPT and cPPT groups showed comparable changes over time. Conclusion Our study did not find significant differences between Positive Psychotherapy with minimal therapeutic supervision and PPT with complete therapeutic supervision. These findings challenge the traditional notion regarding the significance of face-to-face contact and therapist-patient interaction and suggest an economic and efficient alternative to the regular individual face-to-face therapy. As the participants were predominately female, further research should focus on a more gender-equal sample to generalize these findings.